The effect of english vocabulary mastery on sports students' ability to understand and practice training instructions - Meirafoni, Yummi; Angelia, Lusi; Fadlan, Abdur Fadlan Rohim; Pra Adha, Ozha Wahyu; Sepyanda, Marsika (Jurnal Patriot, 2025)
Problems: Most previous English for Specific Purposes (ESP) studies have focused on general language skills rather than the direct impact of vocabulary mastery on students’ ability to comprehend and physically execute training instructions in real-time sports contexts. This study offers a novel contribution by empirically examining how English vocabulary knowledge enhances understanding and practical performance during sports training sessions. Purpose: This study aims to examine the effect of English vocabulary mastery on the ability of sports students to understand and execute training instructions. Methods: A total of 20 students from a physical education program participated in this quantitative study using a paired sample experimental design. Two instruments were employed: a vocabulary test and a performance-based instruction comprehension test. The data were analysed using descriptive statistics, normality tests, a paired t-test, and simple linear regression. Results: The results showed that the average vocabulary score was 74.45 (SD = 11.71), while the average comprehension and execution score was 76.75 (SD = 11.52). The Shapiro-Wilk test confirmed that the data were normally distributed (p > 0.05). The paired t-test revealed a significant difference between vocabulary mastery and instruction performance, with t(19) = -14.04 and p < 0.001. The regression analysis further showed a strong and significant positive influence of vocabulary mastery on instruction performance (R² = 0.9025; p < 0.001). Conclusion: These findings suggest that English vocabulary mastery is crucial in enabling students to comprehend and execute training instructions accurately. This study highlights the importance of integrating sport-specific English vocabulary training into physical education curricula to enhance students’ instructional comprehension and field performance.